2017
DOI: 10.1139/bcb-2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bovine lactoferrin onChlamydia trachomatisinfection and inflammation

Abstract: Chlamydia trachomatis is an obligate, intracellular pathogen responsible for the most common sexually transmitted bacterial disease worldwide, causing acute and chronic infections. The acute infection is susceptible to antibiotics, whereas the chronic one needs prolonged therapies, thus increasing the risk of developing antibiotic resistance. Novel alternative therapies are needed. The intracellular development of C. trachomatis requires essential nutrients, including iron. Iron-chelating drugs inhibit C. trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…This concept should be deeply reviewed in light of the capability of some bacteria to enter and survive inside cells, such as macrophages. Intracellular iron retention could be an inducer of the growth of facultative and obligate intracellular pathogens inside epithelial cells and macrophages, thus increasing infection severity [ 29 , 30 ]. In this respect, the recent discovery of the tight correlation between iron and inflammatory homeostasis must take into account that infectious processes by intracellular bacteria are favored and enhanced by intracellular iron overload, making imperative a strong revision of the classical iron therapy.…”
Section: Iron and Its Homeostasismentioning
confidence: 99%
“…This concept should be deeply reviewed in light of the capability of some bacteria to enter and survive inside cells, such as macrophages. Intracellular iron retention could be an inducer of the growth of facultative and obligate intracellular pathogens inside epithelial cells and macrophages, thus increasing infection severity [ 29 , 30 ]. In this respect, the recent discovery of the tight correlation between iron and inflammatory homeostasis must take into account that infectious processes by intracellular bacteria are favored and enhanced by intracellular iron overload, making imperative a strong revision of the classical iron therapy.…”
Section: Iron and Its Homeostasismentioning
confidence: 99%
“…Recently, several studies have demonstrated the protective activity of vaginal Lactobacillus spp., as well as of other host defense factors present in the healthy cervico-vaginal micro-environment, toward C. trachomatis infection (Mastromarino et al, 2014; Nardini et al, 2016; Sessa et al, 2017a,b). Specifically, it has been showed that Lactobacillus crispatus and Lactobacillus brevis are able to interfere with the early phases of C. trachomatis infection as well as to inhibit its intracellular replication, preventing the dissemination of the infection in the host (Mastromarino et al, 2014; Sessa et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…All the women underwent a complete assessment in three scheduled appointments: at baseline (T0), on the 10th day of treatment (treatment: T1), and 2 weeks after the end of lactoferrin administration (post-treatment: T2). Inclusion criteria were sexually active women of reproductive age (18–45 years old) with regular menstrual cycles and with symptomatic acute BV diagnosed according to Amsel’s criteria [33] and Nugent score [34]. The exclusion criteria were age < 18 years; Nugent score < 7; known active infection due to Chlamydia , yeasts, Neisseria gonorrhoeae , or Trichomonas vaginalis ; clinically apparent herpes simplex infection or defined diagnosed human papillomavirus, herpes simplex virus type 2, or human immunodeficiency virus type 1 infection; pregnancy or breastfeeding; antibiotic, probiotic, or exogenous hormone treatments; and other gynecological conditions that could cause bleeding (polyps, endometrial hyperplasia, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Otsuki and Imai [33] showed that, in women with a history of multiple pregnancy losses or preterm delivery and refractory BV, lactoferrin administration could improve the vaginal microbiota, preventing both cervical inflammation and preterm delivery. Sessa et al [34] reported that intravaginal administration of lactoferrin resolved asymptomatic Chlamydia trachomatis in six out of seven pregnant women and resulted in normal deliveries.…”
Section: Introductionmentioning
confidence: 99%